Analisis Value Engineering Pekerjaan Jalan Pelabuhan Tanjung Kramat Sangkulirang - Pratama, Angga; Tukimun; Nur, Alpian (MoDuluS Media Komunikasi Dunia Ilmu Sipil, 2025)
Large-scale construction projects often face challenges in cost control without compromising the function and quality of the work. One approach to address this issue is Value Engineering (VE), a systematic method aimed at identifying and eliminating unnecessary costs. This study applies the Value Engineering Job Plan method based on the theory of A.J. Dell’Isola (1997), which consists of five phases: information, function analysis, creative, evaluation, and recommendation. The research was conducted on the Tanjung Kramat Sangkulirang Port Road project, focusing on subgrade work, which accounts for a significant portion of the project cost. Based on the analysis, two design alternatives were developed: (1) Preloading + 100 kN Geotextile without PVD, and (2) Embankment reinforced with Geotextile and Geocell. The first alternative achieved a cost saving of IDR 9,166,666,667 or 1.07%, while the second alternative provided a greater saving of IDR 19,404,156,166 or approximately 1.16%. The results indicate that the second alternative is the most economical option for implementation in this project. The application of VE proved effective in achieving cost efficiency without reducing the project's function and quality, making it a strategic approach in construction cost management.